Synthesis of a Linear Fragment Containing the C23-C26 Stereocenters of Phorboxazole: A Flexible Molecule with Defined Conformation - Greer, Patrick B.; Donaldson, William A. (Letters in Organic Chemistry, 2018)
Background: Phorboxazole is a polycyclic natural product which exhibits antitumor activity. The synthesis of C20-C26 segment of phorboxazoles, possessing 5 contiguous stereocenters, is described. Methods: A double diastereoselective aldol reaction using an Evans chiral oxazolidinone with a chiral aldehyde generates the C23-C25 stereocenters. Chain extension via Horner-Wadsworth-Emmons olefination and subsequent functional group manipulation set the stage for introduction of C26 stereocenter via a Sharpless asymmetric dihydroxylation. A Roskamp homologation serves to introduce C20-C21 carbons. Results: The acyclic segment was generated in 13 steps, 7.6% overall yield was obtained from the precursors 4 and 5. Examination of the 3JH-H coupling constants for several of the compounds revealed that they exist in predominantly one conformer. Conclusion: The linear molecules 13, 17, and 18 serve as additional examples of acyclic molecules with defined conformation. The defined conformations of these molecules are due to the presence of a bulky “inductor group”.
Keywords: dihydroxylation